Clinical Efficacy and Residue Depletion of 10% Enrofloxacin Enteric-Coated Granules in Pigs - Lei, Zhixin; Liu, Qianying; Yang, Bing; Xiong, Jincheng; Li, Kun; Ahmed, Saeed; Hong, Liping; Chen, Pin; He, Qigai; Cao, Jiyue (Frontiers in Pharmacology, 2017)
A new, more palatable formulation of 10% enrofloxacin enteric-coated granules was investigated to evaluate the pharmacokinetic effect in plasma, the residue elimination in tissues and the clinical efficacy against Actinobacillus pleuropneumonia (APP) and Mycoplasam suis (MS) in pigs. In this study, the enrofloxacin concentrations in plasma and tissues were detected using high-performance liquid chromatography with phosphate buffer (pH=3) and acetonitrile. The pharmacokinetics and elimination of enrofloxacin enteric-coated granules were performed after oral administration at a single dose of 10 mg/kg﹒body weight (bw) and 5 mg/kg twice per day for 5 consecutive days, respectively. The in vivo antibacterial efficacy and clinical effectiveness of enrofloxacin enteric-coated granules against APP and MS were assayed at 2.5, 5, 10 mg/kg, compared with tiamulin (8 mg/kg) based on establishment of APP and MS infection models. 56 APP strains were selected and tested for in vitro antibacterial activity of enrofloxacin enteric-coated granules. The main parameters of elimination half-life (t1/2β), Tmax and area under the curve (AUC) were 14.99±4.19 h, 3.99±0.10 h and 38.93±1.52 μg﹒h/mL, respectively, revealing that the enrofloxacin concentration remained high and with a sustainable distribution in plasma. Moreover, the analysis on the evaluation of enrofloxacin and ciprofloxacin in muscle, fat, liver and kidney showed that the recovery were more than 84% recovery in accordance with the veterinary drug residue guidelines of United States Pharmacopoeia, and the withdrawal periods were 4.28, 3.81, 4.84 and 3.51 d, respectively, suggesting that the withdrawal period was 5 d after oral administration of 5 mg/kg twice per day. The optimal dosage of enrofloxacin enteric-coated granules against APP and MS was 5 mg/kg, with over 90% efficacy, which was significantly different (p<0.05) to the 2.5 mg/kg group, but not to the 10 mg/kg group or the positive control group (tiamulin). In conclusion, 10% enrofloxacin enteric-coated granules had significant potential for treating APP and MS, and it provided an alternative enrofloxacin palatability formulation.